Phage resistance formation and fitness costs of hypervirulent Klebsiella pneumoniae mediated by K2 capsule-specific phage and the corresponding mechanisms - Tang, Miran; Huang, Zeyu; Zhang, Xiaodong; Kong, Jingchun; Zhou, Beibei; Han, Yijia; Zhang, Yi; Chen, Lijiang; Zhou, Tieli (Frontiers in Microbiology, 2023)
Hypervirulent Klebsiella pneumoniae (hvKP) not only causes invasive infections even in healthy people but also carries the risk of incurable severe infections through convergence with multidrug resistance. As a promising alternative to chemotherapeutic antibiotics, phage has been proposed for the treatment of hvKP infections. Here, we demonstrate that K2 serotype sequence type 86 hvKP FK1979, one of the main pandemic lineages of hvKP with thick capsule polysaccharide (CPS), rapidly develops resistance to a K2-specific lysis phage ΦFK1979 which is well-studied in this work to possess polysaccharide depolymerase. The phage-resistant mutants showed a marked decrease in the CPS expression. Whole-genome sequencing revealed single nucleotide polymorphism (SNP) in genes encoding RfaH, galU, sugar glycosyltransferase and polysaccharide deacetylase family protein in the phage-resistant strains. Genes knockout and complementation revealed rfaH and galU are required for CPS production and phage sensitivity. Quantitative PCR showed significantly decreased expressions in genes involved in the biosynthesis or regulation of CPS and/or lipopolysaccharide (LPS) in the phage-resistant strains. Despite the rapid and frequent development of phage resistance being a disadvantage, the attenuation of virulence and fitness in vitro and in vivo indicated that phage-resistant mutants of hvKP were more susceptible to the immunity system. Interestingly, the newly isolated phages targeting ΦFK1979-resistant mutants changed significantly in their plaque and virus particle morphology implying they have distinct receptors. Genome sequencing and bioinformatic analysis showed that the genomes of phages targeting mutants were much larger than and significantly different from that of ΦFK1979. Phages pR2/pR3/pR4/pR6/pR7 possessed much more functional proteins, which possibly help them to recognize receptors and lyse bacteria more efficiently. Our study suggests that K2-specific phage has the potential to function as an antivirulence agent, or a part of phage cocktails combined with other phages with different receptors, against hvKP-relevant infections.